Future power market and sustainable energy solutions – The treatment of uncertainties in the daily operation of combined heat and power plants. (15th April 2015) - Sorknæs, Peter; Lund, Henrik; Andersen, Anders N.
Highlights: Increasing renewables make electricity system balancing increasingly important. Small-scale combined heat and power plants can provide electricity system balancing. Plants are experiencing decreasing feasibility of combined heat and power units. We simulate a small-scale district heating plant with solar collector fields. Providing electricity system balance can increase feasibility of small-scale plants. Abstract: Intermittent renewable energy sources (RES) are increasingly used in many energy systems. The higher capacity of intermittent RES increases the importance of introducing flexible generation units into the electricity system balancing. Distributed district heating plants with combined heat and power (CHP) can provide this flexibility. However, in electricity systems with a high penetration of intermittent RES, CHP units are currently experiencing decreasing hours of operation, making it likely that existing CHP capacity will be phased out from the energy system. Furthermore, when the plants provide balancing for the electricity system, the complexity of their daily operation planning is increased. This article analyses and discusses how these units can improve their economic feasibility by providing balancing services to the electricity system, benefitting both each individual plant and the system as a whole. This is done by using the case of the Danish district heating plant, Ringkøbing District Heating, which has a relatively high capacity of solar heating installed and is located in an area with a high penetration of wind power. It is found that the plant can increase the economic feasibility of the CHP unit by participating in the electricity balancing tasks; however, it is uncertain whether the benefits are substantial enough to keep the distributed CHP capacity in operation.